The Role of Immunohistochemistry for Primary Oral Diagnosis in a Brazilian Oral Pathology Service. Issue 10 (November 2021) - Araújo, Anna Luíza D.; Fonsêca, Jéssica M.; do Amaral-Silva, Gleyson Kleber; de Lima Morais, Thayná M.; Mariz, Bruno A.L.A.; Fonseca, Felipe P.; Lopes, Marcio A.; Vargas, Pablo A.; Santos-Silva, Alan R.; de Almeida, Oslei P.
Abstract : A proper antibody panel selection is one of the most important factors to reach an adequate diagnosis in challenging cases. This retrospective study was designed to determine the contribution of immunohistochemistry (IHC) in the primary diagnosis of oral diseases in one of the main services of oral pathology in the State of São Paulo, Brazil, and to identify the most common antibodies used, and recommend diagnostic algorithms based on our experience with challenging lesions. A total of 1698 IHC stains were performed in 401 cases from a total of 28, 804 cases received from public dental clinics and private dental practitioners within a period of 13 years, representing a frequency of 1.4% of IHC solicitations. Among these, 112 (28%) were mandatory to reach a final diagnosis and 255 (63.6%) were confirmative. In 34 (8.4%) cases, it was not possible to reach a conclusive/final diagnosis, even with IHC. Regarding the nature of the lesions, 210 (52.3%) were benign, 163 (40.6%) were malignant tumors, 13 (3.2%) were reactive, 10 (2.5%) were premalignant, and 5 (1.2%) were lesions of uncertain malignancy. Small amount of tissue of some incisional biopsies, overlapping features of spindle cell lesions (epithelial, neural, melanocytic, smooth muscle, endothelial, and fibroblastic/myofibroblastic cell differentiation), and overlapping features of salivary gland lesions were the most frequent challenges in which IHC stains were requested. Spindle cell lesions were the most frequent (22%) among all cases that required IHC to reach a final diagnosis. The implementation of IHC for routine practice requires a wide range of markers, proper antibody selection, and knowledge to interpret the subjectivity of staining. The inherent limitation of incisional biopsies was pointed as a reason to inconclusive diagnosis, despite a wide range of antibodies that our laboratory displays.